Hybrid Assembly and Annotation of the Genome of the Indian Punica granatum, a Superfood - Usha, Talambedu; Middha, Sushil Kumar; Babu, Dinesh; Goyal, Arvind Kumar; Das, Anupam J.; Saini, Deepti; Sarangi, Aditya; Krishnamurthy, Venkatesh; Prasannakumar, Mothukapalli Krishnareddy; Saini, Deepak Kumar; Sidhalinghamurthy, Kora Rudraiah (Frontiers in Genetics, 2022)
The wonder fruit pomegranate (Punica granatum, family Lythraceae) is one of India’s economically important fruit crops that can grow in different agro-climatic conditions ranging from tropical to temperate regions. This study reports high-quality de novo draft hybrid genome assembly of diploid Punica cultivar ‘Bhagwa’ and identifies its genomic features. This cultivar is most common among the farmers due to its high sustainability, glossy red color, soft seed, and nutraceutical properties with high market value. The draft genome assembly is about 361.76 Mb (N50 = 40 Mb), ~9.0 Mb more than the genome size estimated by flow cytometry. The genome is 90.9% complete, and only 26.68% of the genome is occupied by transposable elements and has a relative abundance of 369.93 SSRs/Mb of the genome. A total of 30803 proteins and their putative functions were predicted. Comparative whole-genome analysis revealed Eucalyptus grandis as the nearest neighbor. KEGG-KASS annotations indicated an abundance of genes involved in the biosynthesis of flavonoids, phenylpropanoids, and secondary metabolites, which are responsible for various medicinal properties of pomegranate, including anticancer, antihyperglycemic, antioxidant, and anti-inflammatory activities. The genome and gene annotations provide new insights into the pharmacological properties of the secondary metabolites synthesized in pomegranate. They will also serve as a valuable resource in mining biosynthetic pathways for key metabolites, novel genes, and variations associated with disease resistance, which can facilitate the breeding of new varieties with high yield and superior quality.